2019
DOI: 10.18632/oncotarget.27364
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of adenosine kinase isoforms in breast cancer

Abstract: Dysregulated adenosine signaling pathway has been evidenced in the pathogenesis of breast cancer. However, the role of adenosine kinase (ADK) in tumorigenesis remains unclear while it crucially regulates the removal and availability of adenosine. ADK has two isoforms that localize to discrete subcellular spaces: i.e., nuclear, long-isoform (ADK-L) and cytosolic, short-isoform (ADK-S). We hypothesized that these two ADK isoforms would be differentially expressed in breast cancer and may contribute to divergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Adenosine kinase (ADK) is also a key metabolic enzyme in the removal of adenosine that is tightly regulated in healthy cells. Adenosine signaling is associated with breast carcinoma and it is identified that downregulation of ADK decreases proliferation, migration, and invasion of TNBC cells, suggesting a functional role of ADK in TNBC 50 . Our study identified a new 5-gene metabolic signature (comprising of TALDO1, GPI, LDHA, SHMT2, and ADK) that is a more powerful prognostic marker than any of the single genes alone.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine kinase (ADK) is also a key metabolic enzyme in the removal of adenosine that is tightly regulated in healthy cells. Adenosine signaling is associated with breast carcinoma and it is identified that downregulation of ADK decreases proliferation, migration, and invasion of TNBC cells, suggesting a functional role of ADK in TNBC 50 . Our study identified a new 5-gene metabolic signature (comprising of TALDO1, GPI, LDHA, SHMT2, and ADK) that is a more powerful prognostic marker than any of the single genes alone.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, ADK-VCL, TNFRSF9 and LTB, as the top three most connected genes, were identified as novel cancer genes for further investigation. Adenosine kinase (ADK) has an important role in mitosis, tumorigenesis, tumor-associated tissue remodeling, and invasion, and manipulation of ADK has the potential to be a therapeutic strategy for invasive breast cancer [24]. Vinculin (VCL) is a cytoskeletal protein associated with cell-cell and cell-matrix junctions, which interacts with many focal adhesion proteins and has been found to be closely linked to tumor migration [25].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the expression of two ADK isoforms are observed in the cases of breast cancer [62]. The changes in the tumor tissue primarily concerned ADK-L in comparison with healthy tissue.…”
Section: Protein Levelmentioning
confidence: 99%
“…In addition to nervous system disorders [50,52,57], the changes in the level of ADK enzyme attract researchers who study diabetes [58,59], vascular inflammation [60,61], and cancer [5,62].…”
Section: Biological Significance Of Adkmentioning
confidence: 99%
See 1 more Smart Citation